2021
DOI: 10.3389/fsufs.2021.726482
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Reducing the National Milk Deficit and Accelerating the Transition to a Sustainable Dairy Value Chain in Zimbabwe

Abstract: The Zimbabwean dairy industry is massively underperforming, as evidenced by a reduction in milk yield from 262 million liters in 1990 to <37 million liters in 2009 and a steady but slow increase to 82 million liters in 2021. The current demand for milk in Zimbabwe stands at 130 million liters, and there is a national capacity for processing 400 million liters per annum. This study used literature, stakeholder inputs and expert knowledge to provide a perspective on practical options to reduce the nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Several studies have documented the low productivity yields of tropical bovine dairy farming. At the farm level, low milk yields and calving rates, late age at first calving, and long calving intervals prevail and are directly related to nutritional aspects, inappropriate use of breeds, poor farm management, limited disease control, and little technical support (BATEKI et al, 2020;CHIRINDA et al, 2021). These production systems are also characterized by great dependency of external farming inputs and thus remain poorly sustainable and frequently become low-margin endeavors (BAUTISTA et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have documented the low productivity yields of tropical bovine dairy farming. At the farm level, low milk yields and calving rates, late age at first calving, and long calving intervals prevail and are directly related to nutritional aspects, inappropriate use of breeds, poor farm management, limited disease control, and little technical support (BATEKI et al, 2020;CHIRINDA et al, 2021). These production systems are also characterized by great dependency of external farming inputs and thus remain poorly sustainable and frequently become low-margin endeavors (BAUTISTA et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Against this background, a technological change in food systems is needed to overcome the problems of food insecurity and malnutrition. The transition from traditional or low-productive pastures to sustainable forage-based cattle systems with high performance and nutritional quality is one solution that can help the situation [ 18 , 21 , 23 , 24 , 25 ]. The adoption of improved forage materials by cattle producers allows for obtaining quality animal feed and thus food of animal origin in higher quantities and quality.…”
Section: Introductionmentioning
confidence: 99%
“…For farmers, knowledge of environmental effects on performance of animals can significantly increase efficiency of genetic improvement programs. Historically, the Zimbabwe dairy industry has been dual in nature, comprising large scale commercial farms and smallholder multi-enterprise farms that varied with scale of production (Chirinda et al, 2021), Zvinorova et al (2013) observed that several dairy farming systems coexist in the country, being shaped by agro-ecological diversity, differences in human settlement patterns and population density, land tenure, resource endowments, and the resultant economic opportunities available for farmers. Consequently, Gororo (2016) proposed a new dairy classification model where farms are demarcated by dairy herd size and defined in terms of business objectives, production levels, labour organization, feeding systems, resource endowments, use of technology and marketing.…”
Section: Introductionmentioning
confidence: 99%
“…In that classification scheme, dairy farms are categorized by scale into subsistence (< five dairy animals), small scale (family farms, 5-10 dairy animals); intermediate or medium scale (modest investment in dairy, 10-100 dairy animals); and large scale (corporate or family farms, >100 dairy animals). Medium to large scale dairy operations dominate the industry, producing 95-97% of all formally marketed milk in the country (Chirinda et al, 2021). These farms are more mechanized, capitalized and employ semiskilled and skilled labour for all year-round milk production using planted pastures, maize silage, forages and concentrates as feed resources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation